Policy action within urban African food systems to promote healthy food consumption: a realist synthesis in Ghana and Kenya - (:unkn) unknown (My University, 2021)
Background: Obesity and nutrition-related non-communicable diseases (NR-NCDs) are increasing throughout Africa, driven by urbanisation and changing food environments. Policy action has been limited - and influenced by high income countries. Socio-economic/political environments of African food systems must be considered in order to understand what policy might work to prevent NR-NCDs, for whom, and under what circumstances. Methods: A realist synthesis of five policy areas to support healthier food consumption in urban Africa: regulating trade/foreign investment; regulating health/nutrition claims/labels; setting composition standards for processed foods; restricting unhealthy food marketing; and school food policy. We drew upon Ghana and Kenya to contextualise the evidence base. Programme theories were generated by stakeholders in Ghana/Kenya. A two-stage search interrogated MEDLINE, Web of Science and Scopus. Programme theories were tested and refined to produce a synthesised model. Results: The five policies operate through complex, inter-connected pathways moderated by global-, national- and local contexts. Consumers and the food environment interact to enable/disable food accessibility, affordability and availability. Consumer relationships with each other and retailers are important contextual influences, along with political/ economic interests, stakeholder alliances and globalized trade. Coherent laws/regulatory frameworks and government capacities are fundamental across all policies. The increasing importance of convenience is shaped by demographic and sociocultural drivers. Awareness of healthy diets mediates food consumption through comprehension, education, literacy and beliefs. Contextualised data (especially food composition data) and inter-sectoral collaboration are critical to policy implementation. Conclusion: Evidence indicates that coherent action across the five policy areas could positively influence the healthiness of food environ
Keywords: African Research